Strategi Komunikasi Dakwah Jamaah Tabligh Masjid Jami’ Al Burhan Terhadap Anak Punk di Palembang - Mika, Laswan; Syarifudin, Achmad; Hidayat (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "Communication Strategy for the Da'wah of the Tablighi Jamaah Jami' Al Burhan Mosque towards Aunk Children in Palembang." The aim of this research is to find out the strategies used by the Tablighi Jamaah in preaching to punk children in Palembang. In this research the author used a qualitative method with a descriptive approach. Data collection techniques in this research are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The theory used is according to Asmuni Syukir, where in the da'wah strategy there are several principles that must be taken into account so that the da'wah activities are effective and on target, namely Physiological Principles, Sociological Principles, Psychological Principles, the Principles of Dai's ability and expertise and the Principles of effectiveness and efficiency. The results of this research are that in fact the da'wah strategy implemented by the Tablighi Jamaah has been good and successful, because there are a number of punks who have joined the Tablighi Jamaah, while there are those who have not participated because they do not yet have the strength to follow the right path because they have not received guidance. The task of the Tablighi Jamaah is only to invite, while the guidance belongs to Allah SWT.